Idiopathic low molecular weight proteinuria associated with hypercalciuric nephrocalcinosis in Japanese children is due to mutations of the renal chloride channel (CLCN5). - Lloyd, SE; Pearce, S; Günther, W; Kawaguchi, H; Igarashi, T; Jentsch, T; Thakker, R (1997)
The annual urinary screening of Japanese children above 3 yr of age has identified a progressive proximal renal tubular disorder characterized by low molecular weight proteinuria, hypercalciuria, and nephrocalcinosis. The disorder, which has a familial predisposition and occurs predominantly in males, has similarities to three X-linked proximal renal tubular disorders that are due to mutations in the renal chloride channel gene, CLCN5. We have investigated four unrelated Japanese kindreds with this tubulopathy and have identified four different CLCN5 mutations (two nonsense, one missense, and one frameshift). These are predicted to lead to a loss of chloride channel function, and heterologous expression of the missense CLCN5 mutation in Xenopus oocytes demonstrated a 70% reduction in channel activity when compared with the wild-type. In addition, single-stranded conformation polymorphism (SSCP) analysis was found to be a sensitive and specific mutational screening method that detected > 75% of CLCN5 mutations. Thus, the results of our study expand the spectrum of clinical phenotypes associated with CLCN5 mutations to include this proximal renal tubular disorder of Japanese children. In addition, the mutational screening of CLCN5 by SSCP will help to supplement the clinical evaluation of the annual urinary screening program for this disorder.